Forgotten science: How 1900s studies challenge the current research on sap analysis - Santa-Cruz, Javier; Calbucheo, Diego; Valdebenito, Samuel; Vásquez, Vicente; Aguilar, Marcelo; Peñaloza, Patricia; Allendes, Hernán; Vidal, Kooichi (International Journal of Agricultural and Biological Engineering, 2025)
Plant sap analysis has emerged as a key focus in recent agricultural research, aiming to enhance fertilizer management and improve crop nutritional assessment. Despite its current recognition as an innovative technique, the origins of sap testing date back over 120 years, with early studies largely overlooked by contemporary researchers. This work revisits these foundational studies, exploring their findings and revealing their potential to challenge modern techniques. This study discusses historical methods of sap collection and how variations in pressure and extraction techniques can influence its nutrient composition. This retrospective examination suggests that integrating these early insights can significantly enhance current sap testing methods.Keywords: crop nutritional assessment, fertilizer management, on-farm quick tests, plant nutrition, sufficiency valuesDOI: 10.25165/j.ijabe.20251805.9879Citation: Santa-Cruz J, Calbucheo D, Valdebenito S, Vásquez V, Aguilar M, Peñaloza P, et al. Forgotten science: How 1900s studies challenge the current research on sap analysis. Int J Agric & Biol Eng, 2025; 18(5): 317–318.